Tourism in Cuba : casinos, castros, and challenges - Henthorne, Tony L. (Emerald Publishing Limited, 2018)
Tourism in Cuba:Casinos, Castros, and Challenges presents an in-depthexploration of the history and development of tourism in Cuba. Beginning withthe earliest days of prohibition in the US, Tony L. Henthorne illustrates how Cubastrove to position itself as an uninhibited Caribbean playground for thewell-heeled American traveler. This book analyzes the ways in which Cuban tourism reached previously unimagined economic heights through the "new normal" of casinos, night clubs, and prostitution during Fulgencio Batista's reign, and it examines theforces sustaining his rise to power. Fidel Castro's revolution set out to end Batista's reign ofcorruption, promising a new beginning for Cuba and the Cuban people. Casinos were shuttered, and the other hedonistic trappings of decadence quickly vanished; relations between the US and Cuba were severed, and the island begana long transformative relationship with the Soviet Union. This book provides anilluminating insight into the impact of these social and economic changes upon tourism in Cuba. Henthorne goes on to explore Barack Obama's significant travel and economic concessions to Cuba, which resulted in a soar in tourism,and he evaluates how Donald Trump has since scaled back on US overtures to Cuba. He also provides an insider's look at the Cuban tourist product what it was, what it is, and what it may be in the future.
Includes index.
Keywords: Tourism -- Cuba.; Casinos -- Cuba.; Business & Economics -- Industries -- Hospitality, Travel & Tourism.; Tourism industry.; elektronické knihy; electronic books